Perancangan Instrumen Kepuasan Kerja Dosen Di Perguruan Tinggi Z - Rahmi Rismayani Deri; Iwan Satriyo Nugroho (Universitas Insan Cendekia Mandiri, 2020)
Higher education is a service industry, therefore it must be able to provide excellent service. Therefore one of the lecturers’ job satisfaction must be considered. Lecturers who feel job satisfaction will work optimally. InHigher Education Z, it was found that there was an indication of the dissatisfaction of the lecturers’ work, therefore the purpose of this study was to design an Instrumenr of Lecturer performance satisfaction in Higher Education, to find out how high the level of job satisfaction was, and to identify variables from aspects that were not yet optimal Z. The method used is descriptive quantitative. The results of the analysis of the validity test, the value oh the item correlation of each variable, namely form Work, Salary and Wages, promotion Opportunities, Supervision, Co-Workers and Working Conditions by using the formula product moment r value result from 6 variables> r table (0,286) so that the design the job satisfaction instrumrnt is valid. Cronbachs Alpha value reliability test obtained Cronbach’s Alpha value greater than the critical value of (0.60). Then it can be concluded thet the items of the research instrument are reliable. Keywords : Design, Instrument, Job Satisfaction